The Analysis of Ellipsis within The Jakarta Post Cartoons: A Case Study - Arum Priadi (Universitas Ahmad Dahlan, 2014)
AbstractEllipsis mostly occurs in dialogues. When some elements in the dialogue are repeated, they become unnecessary information that lead to redundancy. Therefore, they need to be omitted to achieve effective writing. Nominal ellipsis is ellipsis in nominal group. The positions of modifiers are upgraded to function as Head. The modifiers replacing the position of Head in nominal ellipsis are Deictic, Numerative, and Epithet. Verbal ellipsis is ellipsis in verbal group. It can be specified into lexical and operator ellipsis. When some words are left out in verbal group, they belong to lexical ellipsis. But it is operator ellipsis when the form of be is left out. If the clause becomes the point of departure, it is divided into two parts, namely, modal element and propositional element. Clausal ellipsis is specified into modal and propositional ellipsis. When modal elements are left out, they belong to modal ellipsis. Conversely, it is propositional ellipsis if propositional elements are left out.